Effects of Lactobacillus brevis additives on nutrient composition, fermentation quality, microflora structure and metabolites of Pennisetum giganteum silage - Liao, Juanrui; Liu, Shaona; Yang, Fuhua; Fu, Yurong; Duan, Hanqi; Bao, Xiaowei; Huo, Jinlong; Zhao, Zhiyong (Frontiers in Veterinary Science, 2025)
The current situation of feed resource shortage can be effectively solved by high-value utilization of Pennisetum giganteum. This study investigated the effects of Lactobacillus brevis R-09 on P. giganteum silage quality, microbial structure and metabolites. In a randomized experimental design, silage was treated with (LT: 1.5 × 107 CFU/kg L. brevis R-09) or without (LC: control) inoculant, each replicated six times. The LT group exhibited elevated crude fat (p < 0.05), lactic acid (p < 0.05), and isocaproic acid (p < 0.05) content, alongside reduced crude fiber, butyric acid, and mycotoxin levels (p < 0.05). High-throughput sequencing (16S/18S rDNA) revealed comparable microbial diversity across treatments, with Lactobacillus dominating the bacterial community. Notably, LT increased microbial uniformity and suppressed mold proliferation, diminishing their ecological impact. Liquid chromatography-mass spectrometry (LC–MS) profiling identified 464 differentially abundant metabolites, primarily linked to amino acid and lipid metabolism, suggesting a stabilized metabolic network. Taken together, these results suggest that the addition of L. brevis R-09 can improve the quality of P. giganteum silage by modulating microbial communities and metabolic pathways, thus providing mechanistic insights into the optimization of Lactobacillus-mediated silage fermentation.